Study of Fishery Commodities Cold Chain System at Malang City - Mubarok, Ahmad S.F.Q.R.; Perdana, A.W; Sasmito, B.B; Kusuma, B.; Waluyo, E.; Aji, M.T; Sulthoniyah, S.T.M (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2021)
Fishery commodity distribution system has not been widely studied. Cold chain system must be applied in fishery product distribution system. The study of the cold chain system will be discussed more in this study using a qualitative descriptive approach. The research was carried out with special research procedures related to the COVID 19 protocol. Qualitative data were taken by means of observations and interviews with respondents from fish mongers in traditional markets, Mlijo traders (mobile vegetable vendors) and consumers. The results showed that traditional markets are the sources of food supply in Malang City. The distribution chain shows that Mlijo traders play a major role in distributing fishery products directly to consumers. Consumers are very dependent on Mlijo traders in terms of purchasing daily food ingredients. The cold chain system has not been implemented well in traditional markets, while the cold chain system has been not applied by Mlijo traders.